Investigation of Tribological Properties of Hybrid HDPE Polymer Nano Composites - Abul Kalam Azad, Nursyhira Azad (IRC, 2020)
High-density polyethylene (HDPE) is a thermoplastic polymer, having various applications when used as a primary phase in polymer nanocomposites. However, pure HDPE is vulnerable to fail in tribological properties, particularly bearing applications. Pure HDPE is susceptible to failure in tribological applications owing to the absence of branches in its polymeric chains which make easy for the chain to slide past easily over one another. The high tendency of nanoparticle aggregation in the polymer matrix usually restricts the enhancement in nanocomposite properties. The inter-facial effect between the nanoparticles and the polymer matrix is a critical problem for all types of nanocomposites. Nanofillers (CaCO3/Nano clay) in this research project was developed by masterbatch melt compounding technique.